SIMULATION STUDY FOR IMPROVING PATIENT TREATMENT SERVICES (Journal of Information and Communication Technology, 2003)
This paper describes a simulation study conducted on patients’ waiting time and the optimum use of doctors utilization at the Department of Medicine (MOPD) Hospital Alor Setar (HAS) with the aim of improving the operational performance of the hospital. It incorporates the use of Arena to help MOPD develop a model for the analyses of different alternatives to enhance the doctor utilizations and to improve on the patients’ waiting time. Two different scenarios were considered. The first scenario, which was changing patients’ scheduling capacity resulted in the reduction of patients’ waiting time while the second scenario, which was increasing patients’ appointment capacity by 10% resulted an increase in the use of doctors but at the same time increased patients’ waiting time. Results of the analyses showed that management could reduce patients’ waiting time and increase the use of doctors’ by changing the scheduling strategy and by defining the waiting time itself.